Contributions à la paleontology du Miocène moyen continental du basin du Tage; (IV) Charophytes - Póvoa de Santarém, Pero Filho et Tremês - Soulié-Marsche, I. (2008)
This study on middle Miocene Charophytes from the Tagus' basin indicates the presence of two species, hitherto undescribed from these strata in Portugal. Correlation diagrams of height and width of gyrogonite demonstrate that the populations of Nitellopsis (Tectochara) etrusca from the localities Póvoa de Santarém and Pêro Filho are identical to that from La Grenatière (Hérault, France), The population of Lychnothamnus duplicicarinatus from Tremês is identical to that already known from Anwill (Switzerland). The age of this flora is therefore suggested as being the upper part of the middle Miocene. The results of Charophyte studies are in accordance with stratigraphical conclusions from previously conducted mammalian studies (Antunes and Mein). A table showing the distribution of species in the three portuguese localities is given.